SISTEM INFORMASI BIMBINGAN BELAJAR NUMBER ONE MEDAN BERBASIS WEB - Alex Holyfiel Manullang; Mendarissan Aritonang; Mufria J. Purba (Universitas Methodist Indonesia, 2021)
During increasingly rapid technological developments, one of which is the internet, it is time for manual information processing to be gradually replaced with technological information management. With the development of gadgets and smartphones, which are generally owned by everyone, the availability of information can be obtained through the website. The Web-Based Number One Medan Tutoring Information System is needed as a means of storing information for parents and students who want to know the number one tutoring in the city of Medan. This information system is also a form of promotion, where one of the intermediary media is computers and smartphones. This website can also make it easier for prospective students and parents of students to just know the profile of the number one field guidance. The more parents who register their children to study in the number one field guidance, the faster the number one field guidance can be known by many people.